Cured film and molded article
The active energy curing composition with multifunctional and hydrophilic acrylates, applied to transparent synthetic resin molded products, addresses the issue of water droplet marks by ensuring adequate curing and antifog properties, enhancing substrate permeability and visibility.
Patent Information
- Application Number
- JP2023155681
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-03
AI Technical Summary
Existing anti-fog coatings on transparent synthetic resin molded products suffer from insufficient curing, leading to water droplet marks when exposed to high-temperature steam, which reduces substrate permeability and causes poor visibility and sensor malfunctions.
A cured film formed by an active energy curing composition containing a multifunctional acrylate, a hydrophilic acrylate, and an initiator, with a thickness of 1 μm to 20 μm, ensuring adequate adhesion and antifog properties while preventing water droplet marks.
The solution effectively suppresses the occurrence of water droplet marks, maintains excellent antifog properties, and ensures high adhesion and durability of the cured film, even in low-temperature environments.
Smart Images

Figure 2025047273000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a cured film and a molded article. [Background technology]
[0002] Transparent synthetic resins such as polycarbonate resin (PC) and polymethyl methacrylate resin (PMMA) are excellent in transparency, moldability, and mechanical properties, and are therefore used in many fields, such as outer lenses (translucent covers) for lamps of automobiles and motorcycles, lenses for glasses, covers for optical sensors, and various liquid crystal panels. However, when the surface temperature of a molded product such as a synthetic resin falls below the dew point temperature, moisture in the air condenses into fine droplets, causing fogging. This causes problems such as reduced light transmittance, poor visibility, and malfunction of sensors. In order to prevent such problems, a composition is applied to the surface of the molded product to form a cured film, thereby ensuring transparency.
[0003] For example, Patent Document 1 discloses an anti-fog coating composition characterized by containing a copolymer formed from a monomer mixture including a vinyl monomer having an N-methylol group or an N-alkoxymethylol group, a vinyl monomer having a sulfonic acid group, and an alkyl (meth)acrylate monomer, a basic compound, and a surfactant. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-140589 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the cured film obtained by curing such a composition may be insufficiently cured, and may cause water drip marks due to the elution of uncured components when exposed to high-temperature steam, for example. This may reduce the transparency of the substrate on which the cured film is formed, resulting in poor visibility and malfunction of sensors, etc.
[0006] The present invention has been made in consideration of the above-mentioned points, and has an object to provide a cured film and a molded article that suppress the occurrence of water drip marks. [Means for solving the problem]
[0007] The cured film of the present invention is An active energy curable cured film having a thickness of 1 μm to 20 μm that is cured thinly on at least a part of the surface of a transparent substrate, The cured film has a wavelength of 1625 cm detected by FT-IR analysis ATR method (attenuated total reflection Fourier transform infrared spectroscopy). -1 Peak intensity (A) and 1726 cm -1 The ratio A / B of the peak intensity (B) to the peak intensity (B) of the peak intensity (A) is 0.2 or more and 0.3 or less. [Brief description of the drawings]
[0008] [Figure 1] 1 is a conceptual diagram showing a molded article of the present invention. [Diagram 2] 1A to 1C are diagrams illustrating a manufacturing process of a molded article of the present invention. [Diagram 3] 1 is an FT-IR chart obtained when the cured film of the present invention is measured by FT-IR analysis ATR method (attenuated total reflection Fourier transform infrared spectroscopy). [Figure 4] 1 is a graph showing the correlation between the ratio A / B of the peak intensity (A) at 1625 cm-1 to the peak intensity (B) at 1726 cm-1 detected by measuring an active-energy-curable composition using FT-IR analysis ATR method (attenuated total reflection Fourier transform infrared spectroscopy) and the curing reaction rate (%) of the active-energy-curable composition. [Diagram 5] 1 is a table summarizing the results of comparison between Examples and Comparative Examples of the cured film of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] An embodiment of the present invention will be described. The cured film 10 of the present invention is a cured film obtained by thin-film curing of an active energy curable composition containing a multifunctional acrylate, a hydrophilic acrylate, and an initiator. The thickness of the cured film 10 is 1 μm to 20 μm.
[0010] The multifunctional acrylate is a hydrophobic radical reactive material with high reactivity. By containing the multifunctional acrylate in the active energy ray curable composition, the curing speed of the active energy ray curable composition can be increased. In addition, the highly reactive multifunctional acrylate cures, and the hydrophilic acrylate having a hydrophilic group cures later. Therefore, the multifunctional acrylate that is compatible with the hydrophobic substrate adheres to the substrate 20, and the hydrophilic acrylate that cures later is likely to be arranged on the outermost surface. Therefore, a thin film of the hydrophilic acrylate can be applied to the surface of the cured film 10, and the anti-fogging property can be improved.
[0011] Since the polyfunctional acrylate is hydrophobic, when the polyfunctional acrylate is applied to the hydrophobic substrate 20, the adhesion between the active energy ray curable composition and the substrate can be improved. Therefore, the cured film 10 can be prevented from peeling off from the substrate 20. In addition, since the adhesion between the cured film 10 and the substrate 20 is high, the occurrence of cracks in a low temperature environment can be prevented. Therefore, the cured film 10 having excellent durability can be formed on the substrate 20.
[0012] The content of the polyfunctional acrylate is preferably 15% by mass or more and less than 80% by mass based on the total amount of the active energy ray curable composition. If the content of the polyfunctional acrylate is less than 15% by mass, sufficient adhesion to the hydrophobic substrate cannot be ensured. On the other hand, if the content of the polyfunctional acrylate is 80% by mass or more, the proportion of hydrophilic groups is relatively reduced, and therefore sufficient antifogging properties cannot be imparted to the substrate.
[0013] Examples of polyfunctional acrylates that can be used include pentaerythritol tetraacrylate, PEG200 diacrylate, pentaerythritol hexaacrylate, pentaerythritol triacrylate, pentaerythritol alkoxytetraacrylate, pentaerythritol ethoxytetraacrylate, PEG400 diacrylate, and PEG600 diacrylate.
[0014] The hydrophilic acrylate is a radical reactive material made of a resin component such as a monomer or oligomer. When the active energy ray curable composition is applied to the surface of a substrate 20 (e.g., polycarbonate resin), at least a part of the hydrophilic acrylate is disposed on the surface of the active energy ray curable composition. Then, the active energy ray curable composition is cured by a radical reaction, whereby a cured film 10 having a hydrophilic function can be formed on the surface of the substrate.
[0015] This can reduce the contact angle with water of the surface of the molded body 30 having the cured film 10 formed on the surface of the substrate 20. As a result, moisture diffuses onto the surface of the molded body (cured film) to form a water film, ensuring the anti-fogging properties of the substrate.
[0016] The content of hydrophilic acrylate is preferably 10% by mass or more and less than 50% by mass based on the total amount of the active energy ray curable composition. If the content of hydrophilic acrylate is less than 10% by mass based on the total amount of the active energy ray curable composition, sufficient hydrophilic function cannot be ensured on the surface of the cured film, and fogging of the substrate cannot be prevented. On the other hand, if the content of hydrophilic acrylate is 90% by mass or more, sufficient adhesion to the hydrophobic substrate cannot be ensured.
[0017] Examples of hydrophilic acrylates that can be used include glycerol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol triacrylate, glycerol 1,2-diacrylate, glycerol 1,3-diacrylate, N,N-diethylacrylamide, etc. These radical reactive materials may be used alone or in combination of two or more kinds.
[0018] The initiator is a radical generator that generates highly active radicals when irradiated with ultraviolet light. These radical species undergo decomposition and react with resin components such as monomers and / or oligomers. This reaction product further reacts with another resin component, causing a chain reaction to proceed. Then, the crosslinking reaction proceeds, increasing the molecular weight, curing the radical reactive material and the polyfunctional acrylate, and forming a cured film.
[0019] The content of the initiator is preferably 1% by mass or more and less than 15% by mass based on the total amount of the active energy ray curable composition. If the content of the initiator is less than 1% by mass, the curing of the active energy ray curable composition is insufficient, resulting in curing failure. On the other hand, if the content of the initiator is 15% by mass or more, the molecular weight does not increase, resulting in insufficient strength of the cured film.
[0020] Examples of initiators that can be used include 1-hydroxycyclohexyl phenyl ketone, 2-benzyl-2-(dimethylamino)-4'-morpholinobutyrophenone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone, and 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropan-1-one. It is also preferable to use two or more of these initiators in combination. By using two or more of these initiators in combination, the curing reaction rate of the active energy ray curable composition can be improved.
[0021] In addition to the initiator, the active energy ray-curable composition may contain various additives such as an antibacterial agent, an antifungal agent, an antifoaming agent, an antioxidant, an antistatic agent, a dye, a polymerization inhibitor, an ultraviolet absorber, a light stabilizer, and a leveling agent.
[0022] Examples of antibacterial agents include captan, carbendazim, quinomethionate, chlorothalonil, clozolinate, cyprodinil, epoxiconazole, famoxadone, fenarimol, fenbuconazole, fenfuram, fenpiclonil, azoxystrobin, benalaxyl, benomyl, bitertanol, fluazinam, fludioxonil, fluorimide, fluquinconazole, flusulfamide, flutolanil, folpet, Hexachlorobenzene, hexaconazole, ipoconazole, iprodione, kresoxim methyl, manzeb, maneb, mepanipyrim, mepronil, metconazole, metiram, phthalide, procymidone, propineb, quintozene, tecnazene, thifluzamide, thiophenate methyl, thiram, tolclofos methyl, tolylfluanid, triadimefon, triadimenol, triazoxide, triforine, etc. can be used. Inorganic antibacterial agents can also be used, for example, silver, copper, zinc, tin, lead, gold, etc. Furthermore, synthetic antibacterial agents can also be used, for example, polyhexamethylene hyguanide, hydrochloride, benzethonium chloride, alkyl polyaminoethyl glycine, benzisothiazoline, etc.
[0023] As the mildewproofing agent, for example, sodium dehydroacetate, sodium benzoate, sodium pyridinethione-1-oxide, p-hydroxybenzoic acid ethyl ester, 1,2-benzisothiazolin-3-one and salts thereof can be used.
[0024] Examples of the defoaming agent that can be used include fatty acid salts, liquid fatty oil sulfates, higher alcohol sulfates, fatty alcohol phosphates, fatty acid amide sulfonates, sulfonates of dibasic fatty acid esters, alkylarylsulfonates, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene alkyl esters, sorbitan alkyl esters, polyoxyethylene sorbitan alkyl esters, acrylic polymers, vinyl polymers, and organopolysiloxanes.
[0025] As the antioxidant, for example, a phenol-based antioxidant, a phosphorus-based antioxidant, a sulfur-based antioxidant, etc. can be used. As the phenol-based antioxidant, for example, 2,6-di-tert-butyl-p-cresol, stearyl β-(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate, 1,3,5-trimethyl-2,4,6-tris(3',5'-di-tert-butyl-4-hydroxybenzyl)benzene, etc. can be used. As the phosphorus-based antioxidant, for example, tris(2,4-di-tert-butylphenyl)phosphite, diphenyl mono(2-ethylhexyl)phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)-2-ethylhexylphosphite, distearyl pentaerythritol diphosphite, tri(mononylphenyl)phosphite, etc. can be used. As the sulfur-based antioxidant, for example, dilauryl-3,3'-thiodipropionate, pentaerythritol tetrakis(3-laurylthiopropionate), etc. can be used.
[0026] Examples of the antistatic agent that can be used include various cationic antistatic agents having cationic groups such as primary to tertiary amino groups, quaternary ammonium salts, and pyridinium salts; anionic antistatic agents having anionic groups such as sulfonate groups, sulfate groups, phosphate groups, and phosphonate groups; amphoteric antistatic agents such as amino acid-based and amino sulfate-based; nonionic antistatic agents such as amino alcohol-based, glycerin-based, and polyethylene glycol-based; and polymeric antistatic agents obtained by increasing the molecular weight of the above-mentioned antistatic agents.
[0027] Examples of dyes that can be used include pyrazole azo compounds, anilino azo compounds, triarylmethane compounds, anthraquinone compounds, anthrapyridone compounds, benzylidene compounds, oxonol compounds, pyrazolotriazole azo compounds, pyridone azo compounds, cyanine compounds, phenothiazine compounds, pyrrolopyrazole azomethine compounds, xanthene compounds, phthalocyanine compounds, benzopyran compounds, indigo compounds, and pyrromethene compounds.
[0028] A polymerization inhibitor may be added to prevent the double bond from reacting. Examples of the polymerization inhibitor include hydroquinone (HQ), hydroquinone monomethyl ether (MEHQ), 2,6-di-t-butyl-4-methylphenol (BHT), t-butylcatechol (TBC), and phenol or naphthol derivatives such as 4-methoxy-1-naphthol, phenothiazine derivatives, and nitrosamine salts.
[0029] Examples of ultraviolet absorbers that can be used include octyl methoxycinnamate, dimethoxybenzylidene dioxoimidazolidine octyl propionate, diethylamino hydroxybenzoyl hexyl benzoate, t-butyl methoxydibenzoylmethane, octyl triazone, and 2-ethylhexyl paramethoxycinnamate.
[0030] Examples of light stabilizers that can be used include salicylate-based light stabilizers, benzophenone-based light stabilizers, benzotriazole-based light stabilizers, hindered amine-based light stabilizers, cyanoacrylate-based light stabilizers, oxalic acid anilide-based light stabilizers, and nickel-based quenchers.
[0031] As the leveling agent, for example, a silicon-based leveling agent, an acrylic-based leveling agent, an ester compound, a ketone compound, a fluorine compound, or the like can be used.
[0032] Using FIG. 2, a method for producing a molded body 30 in which a cured film 10 is formed on the surface of a substrate 20 by curing an active energy ray curable composition will be described. First, the active energy ray curable composition is loaded into a paint gun (S1). Then, the substrate 20 to be coated is fixed to a paint jig (S2). The active energy ray curable composition is applied to the surface of the substrate 20 with a paint gun so as to have a uniform film thickness of 10 μm (S3). The active energy ray curable composition is irradiated with ultraviolet rays (S4). The active energy ray curable composition is cured on the surface of the substrate 20 to form a cured film 10 (S5). As described above, a molded body 30 in which a cured film 10 is formed on the surface of the substrate 20 by curing an active energy ray curable composition can be produced.
[0033] When the active energy ray-curable composition is applied to the surface of the substrate 20, it may be applied to a part of the surface of the substrate 20, or it may be applied to the entire surface of the substrate 20. In other words, the cured film 10 may be formed on a part of the surface of the substrate 20, or it may be formed on the entire surface of the substrate 20.
[0034] In this embodiment, the active energy ray curable composition is applied to a uniform thickness of 10 μm to form a uniform cured film 10 of 10 μm on the surface of the substrate 20, but the film thickness may be 1 μm to 20 μm, and is preferably 10 μm to 18 μm. By making the film thickness 10 μm or more, the curing reaction rate of the active energy ray curable composition can be further improved.
[0035] Furthermore, the method for applying the active energy ray-curable composition is not limited to using a paint gun, and application methods using an inkjet or a dispenser may also be used.
[0036] The substrate 20 may be made of a transparent material such as polycarbonate resin (PC), hydrophobic synthetic resin such as polymethyl methacrylate resin (PMMA), or glass.
[0037] The cured film 10 can be used as an anti-fog coating, and the molded body 30 can be used as an outer lens (translucent cover) of a vehicle lamp, a window glass, a lens of glasses, a cover for the surface of an optical sensor, and the like.
[0038] The cured film 10 has a wavelength of 1625 cm detected by FT-IR analysis ATR method (attenuated total reflection Fourier transform infrared spectroscopy). -1 Peak intensity A and wavelength 1726cm -1 The ratio A / B of the peak intensity B (hereinafter referred to as the "A / B value") is 0.2 or more and 0.3 or less.
[0039] 3 shows an FT-IR chart detected by measuring the cured film 10 of the present invention by the FT-IR analysis ATR method (attenuated total reflection Fourier transform infrared spectroscopy). The measurement was performed using a Fourier transform infrared spectrophotometer (model: IRXross) manufactured by Shimadzu Corporation as the measuring device, and a diamond prism.
[0040] As shown by the solid line in FIG. 3, the cured film 10 of the present embodiment is measured by the FT-IR analysis ATR method at a wavelength of 1625 cm -1 The peak intensity (A) of the dotted line on the right is 0.1, and the wavelength is 1726 cm -1 The peak intensity (B) of the peak (dotted line on the left) is 0.4. In other words, the A / B value of the cured film 10 of this embodiment is 0.25.
[0041] Fig. 4 is a graph showing the correlation between the A / B value and the curing reaction rate of the active energy curable composition. As shown in Fig. 4, the A / B value has a high correlation with the curing reaction rate of the active energy curable composition. Since the correlation is a negative correlation, the lower the A / B value, the higher the curing reaction rate of the active energy curable composition tends to be.
[0042] Therefore, the wavelength is 1625 cm -1 Peak intensity (A) and wavelength 1726 cm -1 A cured film having a ratio A / B of 0.2 to 0.3 has a high curing reaction rate of the active energy curable composition and can suppress the occurrence of water drip marks due to insufficient curing of the active energy curable composition. In addition, an A / B value of 0.2 or more can prevent a decrease in the anti-fogging function (hydrophilic function).
[0043] On the other hand, for example, the cured film shown by the dashed line in Figure 3 has a wavelength of 1625 cm -1 The peak intensity (A) of the dotted line on the right is 0.13, and the wavelength is 1726 cm -1 The peak intensity (B) of the peak (dotted line on the left) is 0.35. In other words, the A / B value of the cured film is 0.37. When exposed to high-temperature steam, such a cured film is insufficiently cured, and uncured components of the active energy curable composition are eluted, causing water drip marks. This is mainly caused by insufficient curing of the active energy curable composition.
[0044] Wavelength 1625cm -1 Peak intensity (A) and wavelength 1726 cm -1 The ratio A / B of the peak intensity (A) to the peak intensity (B) is more preferably 0.23 or more and 0.27 or less. When the A / B value is 0.27 or less, the curing reaction rate of the active energy curable composition is further improved, and the occurrence of water drip marks can be further suppressed.
[0045] The cured film 10 of the present invention has a change rate of A / B value of less than 10% before and after acetone cleaning. Here, the measurement after acetone cleaning was performed by immersing the cured film 10 in acetone (CH3COCH3) for 5 seconds, leaving it at room temperature (about 25 degrees) for 10 minutes, and then measuring it by FT-IR analysis ATR method. Since the change rate of A / B value of the cured film 10 before and after acetone cleaning is less than 10%, the cured film 10 has excellent chemical resistance. EXAMPLES
[0046] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0047] Example 1 In a 300 mL separable flask equipped with a stirring blade, 65 parts by mass of pentaerythritol tetraacrylate (product code: P2084 manufactured by Tokyo Chemical Industry Co., Ltd.) as a multifunctional acrylate and 30 parts by mass of glycerol dimethacrylate (product code: B2938 manufactured by Tokyo Chemical Industry Co., Ltd.) as a hydrophilic acrylate were added. Next, 5 parts by mass of 2-benzyl-2-(dimethylamino)-4'-morpholinobutyrophenone (product name: Omnirad369 manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV light to obtain a test piece having a cured film of Example 1 with a film thickness of 8 μm.
[0048] Example 2 In a 300 mL separable flask equipped with a stirring blade, 60 parts by mass of PEG200 diacrylate (product name: PEG200DA manufactured by Daicel Allnex Corporation) as a multifunctional acrylate and 25 parts by mass of polyethylene glycol diacrylate (product code: P2708 manufactured by Tokyo Chemical Industry Co., Ltd.) as a hydrophilic acrylate were added. Next, 15 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184 manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV light to obtain a test piece having a cured film of Example 2 with a film thickness of 10 μm.
[0049] Example 3 In a 300 mL separable flask equipped with a stirring blade, 65 parts by mass of pentaerythritol tetraacrylate (product code: P2084 manufactured by Tokyo Chemical Industry Co., Ltd.) as a multifunctional acrylate and 30 parts by mass of glycerol dimethacrylate (product code: B2938 manufactured by Tokyo Chemical Industry Co., Ltd.) as a hydrophilic acrylate were added. Next, 5 parts by mass of 2-benzyl-2-(dimethylamino)-4'-morpholinobutyrophenone (product name: Omnirad369 manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV light to obtain a test piece having a cured film of Example 3 with a film thickness of 10 μm.
[0050] Example 4 In a 300 mL separable flask equipped with a stirring blade, 65 parts by mass of pentaerythritol hexaacrylate (product code: D5688 manufactured by Tokyo Chemical Industry Co., Ltd.) as a multifunctional acrylate and 30 parts by mass of polyethylene glycol diacrylate (product code: P2708 manufactured by Tokyo Chemical Industry Co., Ltd.) as a hydrophilic acrylate were added. Next, 5 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184 manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV light to obtain a test piece having a cured film of Example 4 with a film thickness of 10 μm.
[0051] Example 5 In a 300 mL separable flask equipped with a stirring blade, 70 parts by mass of pentaerythritol tetraacrylate (product code: P2084 manufactured by Tokyo Chemical Industry Co., Ltd.) as a multifunctional acrylate and 29 parts by mass of polyethylene glycol triacrylate (product code: P2708 manufactured by Tokyo Chemical Industry Co., Ltd.) as a hydrophilic acrylate were added. Next, 1 part by mass of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (product name: Omnirad2959 manufactured by Sanyo Trading Co., Ltd.) was added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV light to obtain a test piece having a cured film of Example 5 with a film thickness of 10 μm.
[0052] Example 6 In a 300 mL separable flask equipped with a stirring blade, 65 parts by mass of pentaerythritol triacrylate (product code: P2084 manufactured by Tokyo Chemical Industry Co., Ltd.) as a multifunctional acrylate and 32 parts by mass of glycerol dimethacrylate (product name: B2938 manufactured by Kyoeisha Chemical Co., Ltd.) as a hydrophilic acrylate were added. Next, 3 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184 manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV light to obtain a test piece having a cured film of Example 6 with a film thickness of 10 μm.
[0053] Example 7 In a 300 mL separable flask equipped with a stirring blade, 50 parts by mass of pentaerythritol alkoxytetraacrylate (product name: EBECRYL 40 manufactured by Daicel Allnex Co., Ltd.) as a multifunctional acrylate and 48 parts by mass of glycerol 1,2-diacrylate (product code: B2938 manufactured by Tokyo Chemical Industry Co., Ltd.) as a hydrophilic acrylate were added. Next, 2 parts by mass of 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropane-1-one (product name: Omnirad127 manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV light to obtain a test piece having a cured film of Example 7 with a film thickness of 10 μm.
[0054] Example 8 In a 300 mL separable flask equipped with a stirring blade, 68 parts by mass of pentaerythritol ethoxy tetraacrylate (product name: P2084 manufactured by Tokyo Chemical Industry Co., Ltd.) as a multifunctional acrylate and 30 parts by mass of glycerol 1,3-diacrylate (product code: B2938 manufactured by Tokyo Chemical Industry Co., Ltd.) as a hydrophilic acrylate were added. Next, 2 parts by mass of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (product name: Omnirad2959 manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV light to obtain a test piece having a cured film of Example 8 with a film thickness of 10 μm.
[0055] Example 9 In a 300 mL separable flask equipped with a stirring blade, 80 parts by mass of PEG200 diacrylate (product name: PEG200DA manufactured by Daicel Allnex Corporation) as a multifunctional acrylate and 15 parts by mass of polyethylene glycol diacrylate (product code: P2708 manufactured by Tokyo Chemical Industry Co., Ltd.) as a hydrophilic acrylate were added. Next, 5 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184 manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV light to obtain a test piece having a cured film of Example 9 with a film thickness of 10 μm.
[0056] Example 10 In a 300 mL separable flask equipped with a stirring blade, 75 parts by mass of PEG400 diacrylate (product name: PEG400DA manufactured by Daicel Allnex Corporation) as a multifunctional acrylate and 20 parts by mass of N,N-diethylacrylamide (product code: D3737 manufactured by Tokyo Chemical Industry Co., Ltd.) as a hydrophilic acrylate were added. Next, 5 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184 manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV light to obtain a test piece having a cured film of Example 10 with a film thickness of 10 μm.
[0057] Example 11 In a 300 mL separable flask equipped with a stirring blade, 70 parts by mass of PEG600 diacrylate (product name: EBECRYL 11, manufactured by Daicel Allnex Co., Ltd.) as a multifunctional acrylate and 25 parts by mass of glycerol 1,3-diacrylate (product code: B2938, manufactured by Tokyo Chemical Industry Co., Ltd.) as a hydrophilic acrylate were added. Next, 5 parts by mass of 2-benzyl-2-(dimethylamino)-4'-morpholinobutyrophenone (product name: Omnirad369, manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV to obtain a test piece having a cured film of Example 11 with a film thickness of 10 μm.
[0058] Example 12 In a 300 mL separable flask equipped with a stirring blade, 20 parts by mass of pentaerythritol tetraacrylate (product code: P2084 manufactured by Tokyo Chemical Industry Co., Ltd.) and 43 parts by mass of PEG600 diacrylate (product name: EBECRYL 11 manufactured by Daicel-Allnex Corporation) were added as a multifunctional acrylate, and 30 parts by mass of glycerol dimethacrylate (product name: B2938 manufactured by Kyoeisha Chemical Co., Ltd.) were added as a hydrophilic acrylate. Next, 7 parts by mass of 2-benzyl-2-(dimethylamino)-4'-morpholinobutyrophenone (product name: Omnirad369 manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV light to obtain a test piece having a cured film of Example 12 with a film thickness of 10 μm.
[0059] Example 13 In a 300 mL separable flask equipped with a stirring blade, 15 parts by mass of pentaerythritol alkoxytetraacrylate (product name: EBECRYL 40, manufactured by Daicel-Allnex Co., Ltd.) and 25 parts by mass of pentaerythritol hexaacrylate (product code: D5688, manufactured by Tokyo Chemical Industry Co., Ltd.) were added as multifunctional acrylates, and 21 parts by mass of glycerol 1,2-diacrylate (product code: B2938, manufactured by Tokyo Chemical Industry Co., Ltd.) and 20 parts by mass of glycerol dimethacrylate (product name: B2938, manufactured by Kyoeisha Chemical Co., Ltd.) were added as hydrophilic acrylates. Next, 9 parts by mass of 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropane-1-one (product name: Omnirad127, manufactured by Sanyo Trading Co., Ltd.) was added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition, which was applied to the surface of a substrate and cured by UV to obtain a test piece having a cured film of Example 13 with a film thickness of 10 μm.
[0060] Example 14 In a 300 mL separable flask equipped with a stirring blade, 50 parts by mass of PEG400 diacrylate (product name: PEG400DA manufactured by Daicel Allnex Co., Ltd.) as a multifunctional acrylate, 20 parts by mass of N,N-diethylacrylamide (product code: D3737 manufactured by Tokyo Chemical Industry Co., Ltd.) as a hydrophilic acrylate, and 23 parts by mass of glycerol dimethacrylate (product name: B2938 manufactured by Kyoeisha Chemical Co., Ltd.) were added. Next, 7 parts by mass of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (product name: Omnirad2959 manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV light to obtain a test piece having a cured film of Example 14 with a film thickness of 10 μm.
[0061] Example 15 In a 300 mL separable flask equipped with a stirring blade, 30 parts by mass of pentaerythritol ethoxy tetraacrylate (product name: P2084 manufactured by Tokyo Chemical Industry Co., Ltd.) and 40 parts by mass of PEG200 diacrylate (product name: PEG200DA manufactured by Daicel-Allnex Corporation) as a multifunctional acrylate, and 24 parts by mass of glycerol 1,2-diacrylate (product code: B2938 manufactured by Tokyo Chemical Industry Co., Ltd.) as a hydrophilic acrylate were added. Next, 6 parts by mass of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (product name: Omnirad2959 manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV light to obtain a test piece having a cured film of Example 15 with a film thickness of 10 μm.
[0062] Example 16 In a 300 mL separable flask equipped with a stirring blade, 30 parts by mass of pentaerythritol ethoxy tetraacrylate (product name: P2084 manufactured by Tokyo Chemical Industry Co., Ltd.) and 40 parts by mass of PEG200 diacrylate (product name: PEG200DA manufactured by Daicel-Allnex Corporation) as a multifunctional acrylate, and 24 parts by mass of glycerol 1,2-diacrylate (product code: B2938 manufactured by Tokyo Chemical Industry Co., Ltd.) as a hydrophilic acrylate were added. Next, 6 parts by mass of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (product name: Omnirad2959 manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV to obtain a test piece having a cured film of Example 15 with a film thickness of 15 μm.
[0063] Example 17 In a 300 mL separable flask equipped with a stirring blade, 80 parts by mass of pentaerythritol hexaacrylate (product code: D5688 manufactured by Tokyo Chemical Industry Co., Ltd.) as a multifunctional acrylate and 15 parts by mass of polyethylene glycol diacrylate (product code: P2708 manufactured by Tokyo Chemical Industry Co., Ltd.) as a hydrophilic acrylate were added. Next, 3 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184 manufactured by Sanyo Trading Co., Ltd.) and 2 parts by mass of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (product name: Omnirad2959 manufactured by Sanyo Trading Co., Ltd.) were added as initiators. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV to obtain a test piece having a cured film of Example 17 with a film thickness of 10 μm.
[0064] Example 18 A 300 mL separable flask equipped with a stirring blade was charged with 40 parts by mass of PEG400 diacrylate (product name: PEG400DA, manufactured by Daicel-Allnex Corporation) and 20 parts by mass of pentaerythritol tetraacrylate (product code: P2084, manufactured by Tokyo Chemical Industry Co., Ltd.) as multifunctional acrylates, and 20 parts by mass of glycerol dimethacrylate (product name: B2938, manufactured by Kyoeisha Chemical Co., Ltd.) and 29 parts by mass of polyethylene glycol triacrylate (product code: P2708, manufactured by Tokyo Chemical Industry Co., Ltd.) and 20 parts by mass of polyethylene glycol triacrylate (product code: P2708, manufactured by Tokyo Chemical Industry Co., Ltd.) as hydrophilic acrylates. Next, 5 parts by mass of 2-benzyl-2-(dimethylamino)-4'-morpholinobutyrophenone (product name: Omnirad369 manufactured by Sanyo Trading Co., Ltd.) and 5 parts by mass of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (product name: Omnirad2959 manufactured by Sanyo Trading Co., Ltd.) were added as initiators. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured by UV to obtain a test piece having a cured film of Example 18 with a film thickness of 10 μm.
[0065] Example 19 In a 300 mL separable flask equipped with a stirring blade, 80 parts by mass of pentaerythritol hexaacrylate (product code: D5688 manufactured by Tokyo Chemical Industry Co., Ltd.) as a multifunctional acrylate and 13 parts by mass of polyethylene glycol diacrylate (product code: P2708 manufactured by Tokyo Chemical Industry Co., Ltd.) as a hydrophilic acrylate were added. Next, 3 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184 manufactured by Sanyo Trading Co., Ltd.) and 4 parts by mass of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (product name: Omnirad2959 manufactured by Sanyo Trading Co., Ltd.) were added as initiators. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV to obtain a test piece having a cured film of Example 19 with a film thickness of 15 μm.
[0066] Comparative Example 1 In a 300 mL separable flask equipped with a stirring blade, 30 parts by mass of EO-modified bisphenol A diacrylate (product name: EBECRYL 150 manufactured by Daicel Allnex Co., Ltd.) as a multifunctional acrylate and 50 parts by mass of N,N-diethylacrylamide (product code: D3737 manufactured by Tokyo Chemical Industry Co., Ltd.) as a hydrophilic acrylate were added. Next, 20 parts by mass of 2-benzyl-2-(dimethylamino)-4'-morpholinobutyrophenone (product name: Omnirad369 manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of an active energy ray curable composition. This was applied to the surface of a substrate and cured with UV light to obtain a test piece having a cured film of Comparative Example 1 with a film thickness of 1 μm.
[0067] Comparative Example 2 In a 300 mL separable flask equipped with a stirring blade, 60 parts by mass of polyester polyol (product name: Polylite OD-X-2420 manufactured by DIC Corporation) as a main component and 10 parts by mass of polyethylene glycol diacrylate (product code: P2708 manufactured by Tokyo Chemical Industry Co., Ltd.) as a curing agent were added. Next, 30 parts by mass of methyl isobutyl ketone (product name: WM44-L70G manufactured by Asahi Kasei Corporation) was added as a solvent. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of a thermosetting composition. This was applied to the surface of a substrate and heated at 80 degrees for 40 minutes to cure, thereby obtaining a test piece having a cured film of Comparative Example 2 with a film thickness of 15 μm.
[0068] (A / B value measurement) The cured films of Examples 1 to 19 and Comparative Example 1 were measured by FT-IR analysis ATR method (attenuated total reflection Fourier transform infrared spectroscopy) to obtain FT-IR charts. 1 Peak intensity (A) and wavelength 1726cm- 1 The ratio A / B of the peak intensity (B) ...
[0069] (A / B value change rate after acetone washing) The cured films of Examples 1 to 19 and the cured film of Comparative Example 1 were measured by FT-IR analysis ATR method (attenuated total reflection Fourier transform infrared spectroscopy) to obtain FT-IR charts. -1 Peak intensity (A) and wavelength 1726 cm -1The A / B value before acetone washing was obtained by calculating the ratio A / B of the peak intensity (B) of the peak intensity (B) of the cured film of Examples 1 to 19 or the cured film of Comparative Example 1. Next, the cured film of Examples 1 to 19 or the cured film of Comparative Example 1 was immersed in acetone (CH3COCH3) for 5 seconds and then left at room temperature (about 25°C) for 10 minutes. Next, the cured film was measured by FT-IR analysis ATR method (attenuated total reflection Fourier transform infrared spectroscopy) to obtain an FT-IR chart. Next, from the obtained FT-IR chart, -1 Peak intensity (A) and wavelength 1726 cm -1 The A / B value after acetone washing was obtained by calculating the ratio A / B of the peak intensity (B) of the peak intensity (A). Figure 5 shows the rate of change in the A / B value after acetone washing for Examples 1 to 19 and Comparative Example 1. The measurement was performed using a Fourier transform infrared spectrophotometer (model: IRXross) manufactured by Shimadzu Corporation as the measuring device, and a diamond prism.
[0070] The rate of change in the A / B value after washing with acetone was calculated using the following formula 1.
[0071] Rate of change (%) = |(A / B value after cleaning - A / B value before cleaning) ÷ A / B value before cleaning × 100|
[0072] (Evaluation of dissolution) A test piece having the cured film of Examples 1 to 19 or the cured film of Comparative Example 1 was placed on a hot plate heated to 90°C, and 20 μL of pure water heated to 50°C was dropped onto the test piece. After that, the drop marks visible after the pure water was evaporated were visually checked to evaluate the dissolution property on a 5-point scale of A to E. The evaluation was performed as follows: A: no trace of the eluted components was visible; B: partial trace of the eluted components was visible; C: trace of the eluted components was thin and spreading; D: clear trace of the eluted components; and E: light was not transmitted due to the eluted components. FIG. 5 shows the evaluation results of the dissolution property of Examples 1 to 19 and Comparative Example 1.
[0073] (Evaluation of anti-fogging properties) The test pieces having the cured films of Examples 1 to 19 or Comparative Example 1 were immersed in 40°C warm water for 240 hours. After that, they were dried at room temperature, and breath was blown onto the test pieces at room temperature. The surface area of the test pieces where fogging occurred was visually confirmed to evaluate the antifogging properties on a 5-point scale of A to E. The evaluation was made as follows: A if no fogging occurred on the test pieces; B if about 10% of the surface area of the test pieces was fogging; C if about 50% of the surface area of the test pieces was fogging; D if about 80% of the surface area of the test pieces was fogging; and E if the entire surface area of the test pieces was fogging. FIG. 5 shows the evaluation results of the antifogging properties of Examples 1 to 19 and Comparative Example 1.
[0074] From FIG. 5, it is clear that the active energy ray curable compositions of Examples 1 to 19 have a sufficient curing reaction rate because the A / B value of the cured film is 0.2 or more and 0.3 or less. In addition, the change rate of the A / B value after acetone washing is 9% or less, so excellent chemical resistance is ensured. Furthermore, in the evaluation of elution, even if traces of eluted components are visible, they are only thin and spread, so excellent elution is ensured. In other words, water drip marks caused by elution of uncured components when high-temperature steam hits the cured film are suppressed. In addition, in this specification, "excellent elution" means that the components contained in the active energy ray curable composition are not easily eluted.
[0075] From the results of Examples 2 to 19, when the thickness of the cured film is 10 μm or more, the A / B value is 0.28 or less, which shows that the reactivity of the active energy ray curable composition is improved. In addition, due to the improvement in the reactivity of the active energy ray curable composition, even if traces of the eluted components are visible in the elution evaluation, they are only partial, which shows that better elution is ensured. Furthermore, since the rate of change in the A / B value after acetone washing is 8% or less, it shows that better chemical resistance is ensured.
[0076] From the results of Examples 16 and 19, when the thickness of the cured film is 15 μm or more, the A / B value is 0.26 or less, which shows that the reactivity of the active energy ray curable composition is improved. In addition, due to the improvement in the reactivity of the active energy ray curable composition, no traces of the eluted components are visible in the elution evaluation, which shows that even better elution is ensured. Furthermore, the change rate of the A / B value after acetone washing is 4% or less, which shows that even better chemical resistance is ensured.
[0077] From the results of Examples 17 to 19, when two or more initiators are used, the A / B value is 0.26 or less, so it is clear that the reactivity of the active energy ray curable composition is further improved. In addition, due to the improvement in reactivity of the active energy ray curable composition, no trace of the eluted component is visible in the elution evaluation, so it is clear that even better elution is ensured. Furthermore, since the rate of change in the A / B value after acetone washing is 4% or less, it is clear that even better chemical resistance is ensured.
[0078] From the results of Example 19, it is clear that when a cured film having a thickness of 15 μm or more is formed and two or more initiators are used, the A / B value is 0.25 or less, and therefore the reactivity of the active energy ray-curable composition is further improved.
[0079] In contrast, in Comparative Example 1, in which the amount of polyfunctional acrylate is as low as 30 parts by mass and the amount of hydrophilic acrylate is as high as 50 parts by mass, poor curing occurs, as can be seen from the A / B value of 0.37. In addition, the change rate of the A / B value after acetone washing is 50%, so sufficient chemical resistance is not ensured. In addition, in the evaluation of elution, the eluted components can be clearly confirmed by visual inspection, and the eluted components prevent the transmission of LED light, so sufficient elution is not ensured. Furthermore, in the anti-fogging evaluation, the entire surface area of the test piece is fogged, so it is clear that sufficient anti-fogging is not ensured.
[0080] Similarly, in the evaluation of elution property of Comparative Example 2, which is a thermosetting composition, the eluted components were clearly visible to the naked eye, and the LED light was not transmitted due to the eluted components, so sufficient elution property was not ensured. Also, in the evaluation of anti-fogging property, about 80% of the surface area of the test piece was clouded, so it is clear that sufficient anti-fogging property was not ensured.
[0081] As described above, the cured film of the present invention can suppress the occurrence of water drip marks. [Explanation of symbols]
[0082] 10 Cured film 20 Base material 30 Molded body
Claims
1. An active energy curable cured film having a thickness of 1 μm to 20 μm that is cured thinly on at least a portion of the surface of a transparent substrate, The cured film has a wavelength of 1625 cm detected by FT-IR analysis ATR method (total reflection Fourier transform infrared spectroscopy). -1 Peak intensity (A) and 1726 cm -1 A cured film having a ratio A / B of 0.2 or more and 0.3 or less to a peak intensity (B) of the peak intensity (A / B).
2. The cured film according to claim 1 , wherein the rate of change in the value of the ratio A / B before and after acetone washing is less than 10%.
3. The cured film according to claim 1 , wherein the ratio A / B has a value of 0.23 or more and 0.27 or less.
4. The cured film according to claim 1, which is formed by curing a thin film having a thickness of 10 μm to 18 μm on at least a part of the surface of the transparent substrate.
5. The cured film according to claim 1 , wherein the transparent substrate is a polymethyl methacrylate resin or a polycarbonate resin.
6. A transparent substrate; a thin active energy curable film having a thickness of 1 μm to 20 μm that is cured on at least a portion of the surface of the transparent substrate; The cured film has a wavelength of 1625 cm detected by FT-IR analysis ATR method (total reflection Fourier transform infrared spectroscopy). -1 Peak intensity (A) and 1726 cm -1 The molded article has a ratio A / B of 0.2 or more and 0.3 or less to the peak intensity (B) of the peak intensity (A / B).
7. The molded article according to claim 6, which is an outer lens of a vehicle lamp.
Citation Information
Patent Citations
Antifog coating composition
JP2011140589A